Anatomical correlates of dynamic auditory processing: relationship to literacy during early adolescence. - Sutherland, M; Zatorre, R; Watkins, K; Hervé, P; Leonard, G; Pike, BG; Witton, C; Paus, T (2012)
Adults show great variation in their auditory skills, such as being able to discriminate between foreign speech-sounds. Previous research has demonstrated that structural features of auditory cortex can predict auditory abilities; here we are interested in the maturation of 2-Hz frequency-modulation (FM) detection, a task thought to tap into mechanisms underlying language abilities. We hypothesized that an individual's FM threshold will correlate with gray-matter density in left Heschl's gyrus, and that this function-structure relationship will change through adolescence. To test this hypothesis, we collected anatomical magnetic resonance imaging data from participants who were tested and scanned at three time points: at 10, 11.5 and 13 years of age. Participants judged which of two tones contained FM; the modulation depth was adjusted using an adaptive staircase procedure and their threshold was calculated based on the geometric mean of the last eight reversals. Using voxel-based morphometry, we found that FM threshold was significantly correlated with gray-matter density in left Heschl's gyrus at the age of 10 years, but that this correlation weakened with age. While there were no differences between girls and boys at Times 1 and 2, at Time 3 there was a relationship between gray-matter density in left Heschl's gyrus in boys but not in girls. Taken together, our results confirm that the structure of the auditory cortex can predict temporal processing abilities, namely that gray-matter density in left Heschl's gyrus can predict 2-Hz FM detection threshold. This ability is dependent on the processing of sounds changing over time, a skill believed necessary for speech processing. We tested this assumption and found that FM threshold significantly correlated with spelling abilities at Time 1, but that this correlation was found only in boys. This correlation decreased at Time 2, and at Time 3 we found a significant correlation between reading and FM threshold, but again, only in boys. We examined the sex differences in both the imaging and behavioral data taking into account pubertal stages, and found that the correlation between FM threshold and spelling was strongest pre-pubertally, and the correlation between FM threshold and gray-matter density in left Heschl's gyrus was strongest mid-pubertally.